Reconciliation of the Javanese-Sundanese Marriage Myth through Symbolism - Endah Nurhawaeny; Muhamad Muhamad (Jurnal Toursci, 2026)
Abstract. The phenomenon of marriage taboos between the Javanese and Sundanese ethnic groups serves as an example of a blend of myths, legends, and folktales. These myths influence the beliefs and attitudes of those who hold them. Aims. The aim of this research is to understand modern society's perspectives on the taboo myths surrounding marriage between the Javanese and Sundanese, as communicated through symbolic interactions by local leaders in Yogyakarta, Surabaya, and Bandung. Methods. This study employs a qualitative descriptive research design to describe the phenomenon of these taboos, drawing on detailed data collected in line with the research problem formulation. The findings indicate that, as part of the social reality, there still exists a small group of modern society who believe in these myths, while others are beginning to abandon the taboo myths surrounding Javanese-Sundanese marriages through the symbolic communication of street names by local leaders in Yogyakarta, Surabaya, and Bandung. Conclusion. The data also shows that Javanese-Sundanese marriages do not pose a problem for divorce. This reality suggests that the passage of time will align with the persistence of myths, which will continue to thrive within Indonesian society's culture.